Effect of Flow Rate NaOH on CO2 Absorption Efficiency Using a Column Tray Absorber - Rizal Arifin; Nurul Faizah; Ardista Izdhihar Kaloka; Anisa Fatma Aulia; Gladys Sukma Thufailah; Muhammad Adnan Syukur (Institut Teknologi Sepuluh Nopember, 2025)
CO2 in industrial gas streams reduces process efficiency, corrodes equipment, and affects product quality. Additionally, CO2 emissions contribute to climate change and global warming. To mitigate these effects, CO2 removal through absorption is essential. Absorption involves contacting a gas mixture with a liquid absorbent to dissolve the gas component. This study examines the effect of CO2 flow rate (V) and NaOH flow rate (L) on CO2 absorption efficiency. The experiment involved preparing 33 liters of 0.1 normal NaOH and 250 milliliters of 0.1 normal HCl, followed by solution standardization using methyl orange. CO2 was introduced through valve V-4 while NaOH was pumped into the absorption column. Samples were taken after steady state was reached, and titration with 0.1 normal HCl determined residual NaOH concentration. Flow rate variations of 1, 3, 5, 7, and 9 liters per minute were tested. Results align with literature, indicating that as CO2 flow rate increases, NaOH flow rate also rises. However, the L/V ratio and absorbed CO2 amount decrease due to reduced contact time, lowering absorption efficiency. This study highlights the importance of optimizing flow rates to enhance CO2 capture.